Talent Management in the Midst of the Dynamics of the Gig Economy: Effective Strategies for Contemporary Organizations - Silalahi, Verry Albert Jekson Mardame (Yayasan Inspirasi Merah Putih Indonesia, 2025)
The gig economy, characterized by flexibility and temporary work arrangements, continues to grow rapidly, especially after the pandemic. While it offers appeal to many workers, this model faces significant challenges in talent management, such as income uncertainty, lack of access to benefits, and limitations in career development. This research aims to explore effective talent management strategies to attract and retain gig workers. The results show that a comprehensive approach is needed, including an efficient hiring process, skills development opportunities, and an inclusive work culture to increase worker engagement and loyalty. Case studies from successful organizations like Uber and Upwork illustrate best practices, including flexible work schedule offerings, financial incentives, and professional development resources. The study concludes that organizations need to continuously evaluate and adjust their talent management strategies to stay competitive. By adopting a holistic approach that is responsive to the needs of gig workers, organizations can not only attract and retain top talent but also contribute to the growth and sustainability of the gig economy as a whole.